Novel poly(ether ketone)arylates: Synthesis, characterization and properties. Issue 5 (22nd January 2013) - Zhou, Yongxiang; Wang, Ning; Li, Min; Wu, Lei; Wu, Ting; Xu, Jianjun; Liu, Pengqing
Abstract In order to reduce the melt temperature (Tm) of the thermotropic crystalline polyarylate and improve its compatibility with poly(ether ether ketone) (PEEK), a series of poly(ether ketone)arylates (PEKARs) containing aryl ether ketone units (AEK) are synthesized through melt transesterification reaction from p‐acetoxybenzoic acid, 1, 3‐bis(4′‐carboxylphenoxy)benzene and 4, 4′‐bis(p‐acetoxyphenoxy)benzophenone. The inherent viscosities of these polymers are in the range 0.35–0.81 dL/g. The morphologies and properties of PEKARs are characterized by polarized optical microscopy, wide‐angle X‐ray diffraction, differential scanning calorimetry, thermal gravimetric analysis, etc. The results show that all PEKARs are semi‐crystalline polymers, and the introduction of AEK units can reduce the symmetry of the main chains, leading to decreasing the crystallizability and changing the crystalline form. The PEKARs with AEK less than 30% can exhibit thermotropic liquid crystalline state. The initial and the maximum decomposition temperatures increase with the increase in AEK content. These PEKARs are expected to act as processing agents for PEEK to reduce its processing viscosity. © 2013 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013